Behavioral Factors Analysis in Investment Decision-Making - Dumohar, Anggiat; Aryotejo, Dimas; Djohan, Nielson; Tirto, Peter; Mulia, Rizki (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2022)
This study focuses in investigating behavioral factors that affect individual investment decision who actively trading in Indonesia stocks exchange. The paper emphasizes in less developed financial markets (Indonesia) to occupy literature gap. Seven (7) human financial behavior which categorized as heuristic biases are measured by numerous questions under online questionnaire, to examine the relationship between trait anxiety, overconfidence, trait anger, self-monitoring, herding factor, anchoring/adjustment, and availability bias with investment decision. To test the hypothesis, sample of 168 Indonesian Stocks Exchange investors are analyzed using statistical methods of regression and correlation analysis. Relationship of financial behavior biases and investment decision is analyzed on the research. The result indicates that overconfidence and self-monitoring are related with investment decision while trait anger, trait anxiety, herding effect and availability bias, and anchoring and adjustment are not related.